HEPATOCARCINOMA CANINO - Sbiacheski, Dianalina Taíla; Beck, Cristiane; Weber, Verônica Metz (Salão do Conhecimento, 2018)
Relato Supervisionado da disciplina de Estágio Clínico II em Medicina Veterinária da UNIJUÍ